Band structure alignment in transfer-free MOCVD grown 2D-TMDC heterostructures revealed by ambient KPFM - M. Abdelbaky; Y. Beckmann; J. Klein; T. G. Fabunmi; N. Stracke; A. Grundmann; M. Heuken; H. Kalisch; A. Vescan; T. Kümmell; W. Mertin; G. Bacher (APL Materials)
Kelvin Probe Force Microscopy (KPFM) under laser illumination is employed to investigate the band structure of MoS2–WS2 heterostructures and its impact on charge carrier separation at the heterointerface. Heterostructures in two distinct stacking orders—MoS2 on WS2 and WS2 on MoS2—were directly grown by metal–organic chemical vapor deposition, i.e., without any mechanical layer transfer processes. This resulted in a pristine interface and efficient interlayer coupling, as evidenced by a uniform work function of 4.6 eV for both stacking orders. Illumination experiments demonstrate the separation of photogenerated charge carriers across the heterointerface as visualized by distinct changes in the surface potential. Utilizing KPFM measurements and augmenting them with Raman and time-resolved photoluminescence data, a relationship between the conduction band minimum and valence band maximum of the heterostructure and the experimentally measured parameters is established. Through this analysis, we identify a lower limit for the heterostructure bandgap of ∼1.2 eV under ambient conditions, which is ascribed to the indirect K–Γ transition. This finding offers critical insights for the deployment of 2D heterostructures in applications such as photodetection devices.